Hydrothermal synthesis and tribological properties of FeS2 (pyrite)/reduced graphene oxide heterojunction. Issue 2 (2nd December 2014) - Zhang, Mingsuo; Chen, Beibei; Tang, Hua; Tang, Guogang; Li, Changsheng; Chen, Lin; Zhang, Hongmei; Zhang, Qing
Abstract : (a) TEM image of FeS2 /RGO-C; (b) curves of friction reduction properties for (1) the paraffin oil, (2) oil with 7 wt% RGO, (3) oil with 7 wt% FeS2, (4) oil with 7 wt% FeS2 /RGO-A, (5) oil with 7 wt% FeS2 /RGO-B, (6) oil with 7 wt% FeS2 /RGO-C. Abstract : An FeS2 (pyrite)/reduced graphene oxide (FeS2 /RGO) heterojunction was synthesized by a facile and effective hydrothermal method. X-ray diffraction proved the high purity of the as-prepared product, and both scanning electron microscopy and transmission electron microscopy showed that FeS2 particles were well distributed on RGO nanosheets with controlled size and morphology. The performance of the FeS2 /RGO composites as lubricating oil additive were investigated on a ball-plate tribotester. The results indicated that FeS2 /RGO could improve the load-carrying capacity dramatically, as well as the friction-reduction and anti-wear properties of the paraffin oil. In addition, higher GO content is beneficial to improve the lubrication properties of FeS2 /RGO composites. The excellent lubrication performance of FeS2 /RGO composites can be attributed to the unique layered structure of FeS2 and RGO.